EFFECT OF ACID AND ALKALI TREATMENTS ON SURFACE AREAS AND ADSORPTION ENERGIES OF SELECTED MINERALS - Jozefaciuk G.; Bowanko G. (My University, 2002)
Bentonite, biotite, illite, kaolin, vermiculite and zeolite were acidified or alkalized with hydrochloric acid or sodium hydroxide at concentrations of 0.1, 1.0 and 5.0 mole dm 3 at room temperature for two weeks. In acid treatments, dissolution of Al prevailed over Si and the opposite was observed in alkali treatments. The XRD patterns showed severe alteration of the crystal structure after acid treatments, whereas sharpening of the XRD peaks after alkali treatments was observed. Illite and kaolin were most resistant to acid attack. With a few exceptions, the surface areas of the minerals computed from both water and nitrogen adsorption isotherms increased with acid and alkali treatments. With increasing reagent concentration, the nitrogen surface area increased faster than the water surface area. Well-defined trends were not noted in either changes of average water or nitrogen adsorption energies or in relative amounts of adsorption sites, indicating that the effects of acid and alkali attack are controlled by the individual character of the minerals.
Keywords: Acidification; Adsorption Energy; Alkalization; Nitrogen Adsorption; Surface Area; WaterVaporAdsorption